Survival Strategy of Rubber Farmers When There is a Decline in Rubber Prices in Ampung Padang Village, Batang Natal District, Mandailing Natal Regency - Aina Zahwa; Sismudjito Sismudjito; R Hamdani Harahap (Budapest International Research and Critics University, 2022)
This research is entitled